How Tempo.co Framed State Partiality in Indonesia's 2024 Presidential Election: Implications for Media Ethics and Democracy - Prayogi, Ichsan Adil; Annisarizki, Annisarizki; Oktaviani, Zalsa Nur (KOMUNIKA, 2025)
The 2024 Indonesian presidential election generated significant controversy, particularly regarding the perceived partiality of the incumbent head of state toward one presidential candidate pair. This controversy was further intensified by the Constitutional Court's ruling on the minimum age requirement for presidential and vice-presidential candidates, which enabled Joko Widodo's son, Gibran Rakabuming Raka, to run as a vice-presidential candidate. This study examines how Tempo.co framed the president's partiality through eight news articles published between January 24 and January 31, 2024, using Murray Edelman's framing analysis. The analysis reveals that Tempo.co consistently and critically framed the president's conduct as an ethical, legal, and moral violation — arguing that a head of state who wishes to campaign should have resigned from office rather than remain in power. Writing in the aftermath of the election — in which Prabowo Subianto and Gibran Rakabuming Raka ultimately won with 58.59% of the national vote — this study positions Tempo.co's critical coverage as a significant case of media accountability during a democratic stress test. The findings carry implications for media ethics, press freedom, and the need for stronger institutional boundaries on executive conduct in future Indonesian elections.